Effect of Progressive Muscle Relaxation Therapy on Stress and Blood Pressure in the Pre-Hypertensive Group - Herdiman, Herdiman; Adawiyah, Dita Rabiatul; Triantika, Triantika; Lindayani, Linlin (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Prehypertension is a condition that precedes the onset of hypertension and typically presents without noticeable symptoms in affected individuals. One of the major contributing risk factors for hypertension among young adults is an unhealthy lifestyle, including elevated stress levels. Objective: This study aims to determine the effect of Progressive Muscle Relaxation (PMR) Therapy on stress and blood pressure among individuals with prehypertension. Method: A quantitative approach was used with a quasi-experimental two-group pre–posttest design involving 40 participants selected through purposive sampling, divided into intervention and control groups. Result and Discussion: The intervention consisted of PMR therapy administered for two consecutive weeks, with each session lasting 20 minutes. Statistical analysis using paired sample t-test showed that, prior to the intervention, 55% of participants in the intervention group experienced moderate stress, with an average blood pressure of 130.80 mmHg systolic and 85.15 mmHg diastolic. After the intervention, 60% fell into the mild stress category, and the average blood pressure decreased to 117.20 mmHg systolic and 76.15 mmHg diastolic. The significance value of 0.000 < 0.05 indicates a meaningful effect of PMR therapy on reducing stress and blood pressure in prehypertensive individuals. Conclusion: This therapy effectively enhances relaxation, reduces muscle tension, and serves as a beneficial nonpharmacological intervention for community use.